Nutritional value of conventional, wild and organically produced fruits and vegetables available in Baja California Sur markets - Pablo Misael Arce-Amezquita; Felix Alfredo Beltrán-Morales; Gisela Alejandra Manríquez-Rivera; Mariams Elizabeth Cota-Almanza; Atenas Quian-Torres; Rosa Guadalupe Peralta-Olachea (Terra Latinoamericana, 2019)
Consuming fruits and vegetables plays a crucial role in the development of age-related diseases including arthritis, diabetes, cancer, atherosclerosis, vascular diseases and metabolic syndromes caused by oxidative stress. Demand for organic food is on the rise, reflected in a significant 11% growth in the organic food trade in the United States, the world’s largest organic market. More farmers are currently producing on more certified organic land, and to date 179 countries have reported activities in organic agriculture. Vegetables analyzed for this study were obtained from commercial shopping centers of the city of La Paz Baja California Sur and were classified into four groups: tomatoes, peppers, citrus fruit and leafy vegetables and subgrouped into conventional, wild and organically produced. The 1,1-diphenyl-2-picrylhydrazyl (DPPH) technique was used to measure the antioxidant activity of the plant extracts. Of the organically produced group, grape tomatoes with 1.273 mg trolox equivalent mg per gram of sample and certified organic bell pepper with 1.119 mg trolox equivalent per gram presented the highest antioxidant power. Of the group of citrus fruits, we found that the wild naranjitas had higher antioxidant power with 1.623 mg trolox equivalent per gram of sample. Finally, of the leafy vegetable group, wild greens (quelites) showed the highest antioxidant power with 1.313 mg trolox equivalent per gram of sample.